Penatalaksanaan Holistik pada Remaja Laki-Laki dengan Urtikaria Kronik Tanpa Angioedema et causa Rangsangan Fisik - Veronica Debora; Reni Zuraida (CV. Jasa Sukses Abadi, 2020)
Urticaria is skin disease characterized by the sudden appearance of wheals and/or angioedema. Chronic urticarial is characterised by the recurrence of hives/angioedema for >6 weeks. The disease is a common and important clinical problem in care and treatment so that it becomes a diagnostic and therapeutic challenge. This study is a case report. Primary data obtained through history taking, physical examination, and home visits. Secondary data were obtained from the patient's medical record. At the first visit, the patient’s complaints were obtained which appeared reddish bumps on the neck, chest, back, both arms and thighs. Internal risk factors in patients are the lack of patient knowledge about the disease they are experiencing, as well as the causes/factorsat influence it and how to prevent the disease, curative treatment patterns, lifestyle: frequent swimming in the river during the day, bathing habits that are less clean and irregular . External risk factors for patients are families seeking medical treatment if complaints are already disturbing (hygiene around the outside of the house is lacking), neighborhoods and playgrounds in dense residential areas surrounded by rice fields. The second visit was an intervention with a family conference method using pictorial leaflet media. The third visit showed complaints of redness and red itching due to the patient taking loratadine 10 mg and dexamethasone 0.5 mg. Patients already have better lifestyle patterns such as maintaining personal hygiene and the environment. There is an increase in patient knowledge about the disease experienced, as well as the causes / factors that influence it and how to prevent the disease experienced, characterized by an increase in post-test scores by 6 points.